ENHANCED AS STRENGTHENING FEED FOR THE GROWTH OF MALES OF HAIR SHEEP CROSSES RELEASED TO COWS - Asmara Sari Nasution; Efi said ali (Jurnal Scientia, 2023)
A sheep required sufficient nutrients for growth. The purpose of this study was to determine the effect of sago pulp (A metro-xylone sago) in various levels of administration in rations of growth male cross hair sheep in weaning for 8 weeks. This paper described using a completely randomized design (CRD) non factorial consisting of 4 treatments with 5 replications. The treatments were as follows: PO = 100% field grass, P1 = 30% field grass + 70% reinforcement feed (based sago pulp 30%), P2 = 30% Field grass + 70% reinforcement feed (based sago pulp 40%), P3 = 30% field grass + 70% reinforcement feed (based sago pulp 50%). Parameters measured were daily weight gain (PBBH) in (g/head/day), feed consumption (g/head/day) and feed conversion. The result showed that highest daily weight is (P1) with weight gain 46,78 (g/head/day) and significant effect to (P0) with lowest weight gain 37,14 (g/head/day). Highest feed consumption is (P1) with consumption 525,57 (g/head/day) while the lowest (P0) 379,46 (g/head/day) and highest feed conversion is (P2) 11,81 while the lowest (P0) 10,22 and effect no significant